Penerapan Logika Fuzzy Sugeno Untuk Optimasi Kualitas Tempe Pada Proses Fermentasi - Rahman Sari, Arfani; Sriani (JURNAL FASILKOM, 2023)
Determining the amount of tempeh production can be done by industries or businesses that process soybeans into tempeh, which is a source of nutrition and food for the Indonesian people. Apart from being easy to get, tempeh is also one of the favorite foods among all groups. In producing tempeh, it is certain that the tempeh manufacturing industry also carries out a fermentation process every day to produce a lot of tempeh, apart from that, the process requires maximum manufacturing so that the quality of the tempeh is maintained until it reaches consumers. However, if it is not optimal, the quality of tempeh and the entrepreneur will lose profits. Therefore, tempeh quality was optimized. In order to reduce the impact of poor quality during the manufacturing process, it is necessary to calculate the prediction factors for the impact of poor quality, namely by using the Sugeno fuzzy logic method. Where fuzzy can be relative and can provide solutions to problems encountered in the production process. Optimizing the quality of tempeh from several variables can be determined by a MAPE value of 7.02% according to the predicted value table of 7.02% and this includes good research and is very efficient. Based on these problems, the author models an application system built with Matlab software.